2019
DOI: 10.1097/bco.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparative study of patient satisfaction following ambulatory outpatient and inpatient total shoulder arthroplasty

Abstract: Background: Little is known about patient perceptions of outpatient total shoulder arthroplasty (TSA). We evaluated patient-reported satisfaction with TSA in a freestanding ambulatory surgery center (ASC) and an inpatient (INPT) setting. Methods: Patients were mailed a survey regarding hospital admission, surgical site infections, and medical problems after surgery, as well as their satisfaction with the surgery and location. Patients were asked if, giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 14 publications
0
42
0
1
Order By: Relevance
“…Of these studies, 2 were removed owing to overlapping patients. 6 , 25 Thus, 7 studies accounting for 937 patients were ultimately included in the final qualitative assessment. 4 , 8 , 12 , 16 , 22 , 23 , 26
Figure 1 PRISMA flowchart of study selection.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these studies, 2 were removed owing to overlapping patients. 6 , 25 Thus, 7 studies accounting for 937 patients were ultimately included in the final qualitative assessment. 4 , 8 , 12 , 16 , 22 , 23 , 26
Figure 1 PRISMA flowchart of study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…However, three of these studies had overlapping patient data sets, and thus the study with the largest patient cohort was included and the two others by the same senior author were removed. 6 , 16 , 25 Owing to the absence of randomized controlled trials, pooled statistics and formal meta-analysis was not performed to avoid potentially inaccurate conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…This requires tremendous cooperation across several stakeholders such as surgeons, anesthesiologists, nurses, administration, insurance agencies, and rehabilitation services [15]. Several studies have shown that adjusting patient expectations, proper patient education, inquiry about living status such as the availability of assistance at home, and proximity to the surgical centre are crucial when considering outpatient pathways [16][17][18][19]. Furthermore, pain management should be carefully planned with the anaesthetists which can include preemptive analgesia, brachial plexus catheters, interscalene blocks, peri-articular injections, and post-operative multimodal pain management [16,20].…”
Section: Level Of Evidence: III Therapeuticmentioning
confidence: 99%
“…The total number of the population included was 199,662 cases of TSAs, with 7637 (3.8%) patients who underwent outpatient TSAs, and 192,025 (96.2%) patients underwent inpatient TSAs. Eight [8,16,17,19,[25][26][27][28] out of the ten studies reported readmission rates and nine studies reported postoperative complications. Two studies [8,25] reported costs in the form of total charges or cost per patient, and one study [18] reported shoulder functional scores.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the total of 37,652 reporting implant used: 34,939 (92.8%) participants underwent aTSA, 2705 (7.2%) underwent rTSA and 8 (0.02%) had HA. 1,[17][18][19][20][21][22][23][24][25][26][27] Of all, 52.9% reported the use of nerve blocks as adjuncts to anaesthesia, this equated to 9.9% of all participants included having a documented nerve block (Supplemental Table 3). The top three most prescribed analgesics were oxycodone (38.9%), paracetamol/acetaminophen (33.3%) and gabapentin (27.8%).…”
Section: Study Variabilitymentioning
confidence: 99%